Some Spirurid Nematodes (Spirurida) from Freshwater and Brackish-Water Fishes in Okinawa Prefecture, Japan, with Descriptions of Two New Species - Moravec, František; Nagasawa, Kazuya (Acta parasitologica, 2021)
PURPOSE: Despite the fact that Okinawa Prefecture represents a very interesting subtropical region of Japan, its fauna of nematodes parasitizing fishes is still little-known. Therefore, new data are needed to recognize the species composition of these parasites in this zoogeographically remarkable region. METHODS: Helminthological examinations of some freshwater and brackish-water fishes in Okinawa Prefecture carried out in the years 2010, 2016 and 2018, revealed two new and four insufficiently known species of spirurid nematodes (Spirurida), all gastrointestinal parasites. These were studied with the use of light and scanning electron microscopy. RESULTS: All nematode species recorded are described: Rhabdochonidae: Rhabdochona honshuensis Moravec et Nagasawa, 1989 from Glossogobius celebius (Valenciennes) (Gobiidae, Perciformes) (new host), Rhabdochona iriomotensis sp. nov. from Ophieleotris sp. (Eleotridae, Perciformes) and Rhabdochona sp. (only females) from Eleotris acanthopoma Bleeker and E. fusca (Forster) (both Eleotridae, Perciformes); Cystidicolidae: Spinitectus mirabilis sp. nov. from Kuhlia rupestris (Lacepède) (Kuhliidae, Perciformes) and Spinitectus sp. larvae from E. acanthopoma; and Camallanidae: Procamallanus (Spirocamallanus) sp. (fourth-stage larva) from Yongeichthys criniger (Valenciennes) (Gobiidae, Perciformes). Rhabdochona iriomotensis sp. nov. is very similar to R. honshuensis, but differs from it in the presence of well-developed ventral precloacal ridges. Spinitectus mirabilis sp. nov. differs from its congeners and all other cystidicolids in having eggs provided with both lateral swellings and polar filaments. CONCLUSIONS: In addition to the discovery of two new nematode species, Rhabdochona iriomotensis sp. nov. and Spinitectus mirabilis sp. nov., the findings of all other species represent new host and geographical records. Rhabdochona denudata honshuensis Moravec et Nagasawa, 1989 is elevated to the level of an independent species R. honshuensis.
Keywords: Parasitic nematode; nemoci ryb; Spinitectus; Fish Diseases; ryby; Japonsko; Female; Nematoda; Microscopy, Electron, Scanning; Procamallanus (Spirocamallanus); Spirurida; zvířata; Fish; Japan; Rhabdochona; sladká voda; hlístice; Fishes; ženské pohlaví; East Asia; Fresh Water; mikroskopie elektronová rastrovací; voda; Water; Animals